Edukasi Kesadaran Ruang Terbuka Hijau dan Lingkungan Hidup di Kawasan Ibu Kota Nusantara: Edukasi Kesadaran Ruang Terbuka HIjau dan Lingkungan Hidup di Kawasan Ibu Kota Nusantara - Sari, Dharwati P; Putri, Resty Intan; Kholifah, Nur Asriatul; Utomo, Pandu K. (Retii, 2024)
The development of the Capital City of the Archipelago (IKN) emphasizes the principle of sustainability and is expected to be able to become a â€œlovable cityâ€ or a city that is loved by its inhabitants and a â€œliveable cityâ€, a city that is livable. The relocation of the National Capital not only brings opportunities but also challenges for the people of East Kalimantan, if the community does not take part in utilizing the momentum of IKN development, it is likely that they will only be spectators later. Along with its development, there is an increase in infrastructure development which results in reduced green open space in this area. Green open space has an important role in maintaining ecosystem balance and environmental quality. The purpose of this Community Service activity is to increase community participation and encourage community participation in efforts to preserve Green Open Space (RTH) and the environment. The target in this activity is the community around the IKN Nusantara area with a total of 40 people from villages or neighborhoods in Sepaku District. The results of this activity are the understanding of residents about the importance of structuring green spaces and tree planting actions as a form of preserving the IKN Nusantara area.